Task Design and Implementation as a Two-way Activity: The Case of Preschool Teachers - Tsamir, Pessia; Tirosh, Dina; Levenson, Esther; Barkai, Ruthi; Tabach, Michal (Scientia in educatione, 2014)
This paper demonstrates how professional development which focuses on task design principles can impact on what a preschool teacher may learn from implementing that task which in turn may impact on changes made to specific task features. Specific design principles for preschool mathematics tasks are presented and exemplified